Effects of vegetable oil coating on soybean meal: Ruminal digestibility and fermentation characteristics through in vitro study: Vegetable Oil Coating on Soybean Meal - Domingga , Aurelia Putri; Astuti, Andriyani; Widyobroto, Budi Prasetyo; Elsabagh, Mabrouk; Paradhipta, Dimas Hand Vidya (Journal of Advanced Veterinary Research, 2026)
This study aimed to evaluate the efficacy of sunflower (SFW), corn (CRN), soybean (SOY), and canola (CNL) oils as natural protein protectants for soybean meal (SBM) in ruminant diets. The primary objectives were to assess their ability to reduce ruminal protein degradation, alter nutrient composition, as well as influence ruminal fermentation, digestibility, and methane mitigation potential. SBM was coated with 5% of each vegetable oil, air-dried, and oven-stabilized. Rumen buffer was prepared by mixing rumen fluid and McDougal solution at a ratio of 1:4. Uncoated SBM (CON) and all dietary treatments were incubated with 50 mL rumen buffer for 48 h at 39 °C. During incubation, the gas pressure was collected at 3, 6, 12, 24, and 48 h. The results showed that oil coating significantly increased dry matter (DM) (p=0.020) from 92.61% to 95.16–95.42% and ether extract (p=0.003) from 0.44% to 0.77–2.41%. Meanwhile, it reduced organic matter (p=0.012) from 65.34% to 54.45–63.05%, compared to dietary CON. In the ruminal digestibility, all dietary treatments reduced (p=0.002) DM digestibility from 69.84% to 51.35–55.97% and total degradable fraction from 25.57 to 19.71–22.05 (p<0.001). Crude protein digestibility varied among oils (p=0.008), with SFW (47.21%) and CRN (32.16%) showing the highest protection, followed by CNL (54.98%) and SOY (72.63%). In fermentation characteristics, all dietary treatments had no effect on rumen pH, ammonia-N, and total VFA production. These results suggest that sunflower and corn oils can serve as effective natural protectants for soybean meal protein, preserving its post-ruminal value without compromising rumen fermentation characteristics.